2017
DOI: 10.1097/coc.0000000000000110
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Ratio-based Staging System Outperforms the Seventh AJCC System for Gastric Cancer

Abstract: Lymph node ratio significantly decreases the stage migration caused by inadequate examined lymph nodes. The advantage of TNrM was validated with a patient cohort from the Eastern medical center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…In this present study, Nr stage was shown to have better discriminatory ability and more accurately prediction than N. Although there was no predictive difference for patients with retrieved lymph nodes ≥ 15, Nr stage revealed superiority in survival prediction for patients with retrieved lymph nodes < 15, demonstrating that Nr stage would better compensate for N stage shortcomings in gastric cancer patients, which is consistent with previous studies [10, 22, 23]. Additionally, a modified staging system, TNrM staging system based on Nr stage, predicted more accurately on overall survival by comparison of the current TNM staging system according to the findings in our study (Figure 3), which was consistent with the findings mentioned in previous investigations [6, 11, 16, 17, 24]. To show the improvement we got in this study, we also validated the various cutoff points produced in previous studies, which was not commonly done by previous authors, and found that the Nr stage, categorized by our cutoff points: 0, 0.15, 0.40 could produce the best prognostic discriminatory ability and predictive accuracy.…”
Section: Discussionsupporting
confidence: 93%
“…In this present study, Nr stage was shown to have better discriminatory ability and more accurately prediction than N. Although there was no predictive difference for patients with retrieved lymph nodes ≥ 15, Nr stage revealed superiority in survival prediction for patients with retrieved lymph nodes < 15, demonstrating that Nr stage would better compensate for N stage shortcomings in gastric cancer patients, which is consistent with previous studies [10, 22, 23]. Additionally, a modified staging system, TNrM staging system based on Nr stage, predicted more accurately on overall survival by comparison of the current TNM staging system according to the findings in our study (Figure 3), which was consistent with the findings mentioned in previous investigations [6, 11, 16, 17, 24]. To show the improvement we got in this study, we also validated the various cutoff points produced in previous studies, which was not commonly done by previous authors, and found that the Nr stage, categorized by our cutoff points: 0, 0.15, 0.40 could produce the best prognostic discriminatory ability and predictive accuracy.…”
Section: Discussionsupporting
confidence: 93%
“…For example, in 2 different reports from Japan, 13,20 median TNLE was 11 in a series of 320 patients and, amazingly, in a separate series of 110 patients undergoing surgery for PHCC, the median TNLE was 24. 12,19 The current study consisted of 437 patients with PHCC with a median TNLE of 3 (IQR 1 to 7), which was similar to other published experiences from Western centers. 18,45 Specifically, we noted that 117 (26.8%) patients had only 1 to 2 LNs examined, 64 (14.6%) had 3 to 4 LNs, and 185 (42.3%) patients had ≥4 LNs examined.…”
Section: Discussionmentioning
confidence: 76%
“…28 In patients with the same N stage, Nr stage improved discrimination of patients' survival. [29][30][31] However, the efficacy of radiotherapy for patients with different N or Nr stage remains unclear.…”
mentioning
confidence: 99%